Fungal-derived Nutraceuticals & Bioactive Compounds with Physiotherapeutic and Health- promoting Properties: A Comprehensive Review - Dr. Mukesh Chander (International Journal of Fungi, 2025)
Fungal-derived nutraceuticals represent a rapidly expanding field in biomedical research, offering a rich source of bioactive compounds with diverse therapeutic applications. This comprehensive review examines the physiotherapeutic and health-promoting properties of fungal metabolites, including polysaccharides, terpenes, proteins, peptides, alkaloids, fatty acids, vitamins, and minerals. Fungi produce over 9,000 bioactive compounds from approximately 22,500 microbial metabolites, with less than 5% of the fungal kingdom explored [1] . The major bioactive constituents demonstrate significant immunomodulatory, anticancer, antioxidant, antimicrobial, anti- inflammatory, neuroprotective, and cardioprotective activities through multiple molecular mechanisms. Clinical trials have validated the therapeutic potential of medicinal mushrooms in cancer adjuvant therapy, immune enhancement, and metabolic disorders with excellent safety profiles [2] . However, challenges remain in standardization, bioavailability optimization, and understanding drug interactions. This review provides comprehensive tables of fungal bioactive compounds, their mechanisms, clinical applications, and safety considerations, highlighting the immense potential of fungal-derived nutraceuticals in modern healthcare.
Keywords: Anti-inflammatory; Bioactive Molecules; Immunomodulation; Neuroprotective; Physiotherapeutics; anticancer